Physical characteristics of materials of Ecuadorian origin for water treatment. Issue 1 (December 2021) - Mayacela, M; Maldonado, L; Morales, F; Suquillo, B
Abstract: In Ecuador, contaminated water is discharged directly into the sewage system. The treatments carried out for the elimination of wastewater pollutants are classified into three types: Physical, Chemical and Biological. One of the treatments that is frequently used is the physico-chemical treatment in which various reactive substances are used, which is why in this research several reactive substances of Ecuadorian origin, including activated carbon, peat, limestone, volcanic pyroclasts, zeolite clinoptilolite and zeolite modernite, are physically characterized. For this purpose, some laboratory tests were carried out based on national and international standards in order to obtain the granulometry, compactness coefficient, porosity, sphericity and permea-bility.